Experience or Perception of Elite Female Athletes on Menstrual Performance or Achivement In Sports Competitions in Bali - Mulyanti, Febrilia Putri; Widiawati , Prisca; Supriatna, Supriatna; Hasanah, Zumroh (Indonesian Journal of Sport Management, 2024)
The purpose of this study is to determine the experience or perception of elite female athletes on the menstrual cycle towards performance or achievement in sports competitions in Bali. The research method used is descriptive quantitative, to strengthen the data in this study, the researcher used a survey approach with data collection using a questionnaire. Data analysis using univariate analysis aims to describe all the variables studied. The subjects used were elite female athletes in the province of Bali, with a sample of 40 female athletes aged 13-40 years. This study was conducted in June 2024 on athletes from the province of Bali. Data analysis using univariate analysis aims to describe all the variables studied. The results of the study showed a negative impact of menstruation on athlete performance 17 (42.5%), athletes who were positively affected by menstruation 3 (7.5%), while athletes who did not feel any difference in the impact of menstruation 14 (35%). The conclusion of this study is that there is a negative impact of menstruation on athlete performance on the day of the competition. Suggestions for athletes to better understand the menstrual cycle, suggestions for coaches to motivate athletes to be able to train better even during menstruation.